A principled approach to skill acquisition in competitive surfing: Embracing representative learning design - Dann, R.; Duhig, S.; Roberts, L.; Kelly, V.; Renshaw, I.; Headrick, J. (International Journal of Sports Science & Coaching, 2024)
The recent rise in professionalisation and institutionalisation of competitive surfing has resulted in a dramatic increase in the use of alternative training modalities. These are often employed in an attempt to increase exposure to surf-like activities when appropriate ocean conditions are not available. It is commonly accepted that practice sessions should be grounded in theory, with training content informed by a clear scientific rationale. Despite this, research is yet to offer surfing coaches and surfers effective strategies to assist in implementing appropriate `off water` training modalities. It is widely accepted that integrating a representative learning design is crucial towards the transfer of performance to competition environments. Therefore, the aim of this paper is to promote representative learning design (RLD) as a contemporary, principled framework that can underpin the creation of surfing training design and performance. Examples of constraints relevant to surfing are considered, and the efficacy and rationale of popular training methods are challenged. Finally, practical implications and coaching tools to underpin the implementation of representative learning design in surf training are provided.